AGRIBISNIS PERKEBUNAN MEMASUKI AWAL ABAD 21: BEBERAPA AGENDA PENTING - WAYAN R. SUSILA; BAMBANG DRADJAT (SOCA: Jurnal Sosial Ekonomi Pertanian, 2001)
Estate-crop agribusiness has played and is still expected to play important roles inIndonesian economy. Besides its consistent contribution on economic growth and foreignexchange earning, it provides employment for more than 13 million people. In the beginningof 21st century, the estate-crop agribusiness will face various new important agenda andstrategic business environment changes related to this subsector, namely, production cost,commodity prices, market competition, trade liberalization, production policies, trade policies,regional autonomy, environmental issues, and plantation plundering. Some of them willdepress the development of the subsector in the beginning of 21st century, while the otherswill provide better opportunities for the development of the subsector or their net impacts arestill vague. To optimize the roles of the estate-crop subsector agribusiness, various importantagenda and strategic business environment changes related to the subsector should bemanaged in a such way that the negative impacts of the changes can be minimized while thepositive and vague impacts can be converted to be a growth engine of the subsector inentering the beginning of 21th century.